Perbaikan Kualitas Citra Menggunakan Metode High Pass Filter dan Sharpening - Kahirunisa; Chandra Frenki Sianturi (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2020)
Many events can be recorded or immortalized as a reminder, the current image is the need of many users, users often distort the quality of the image so that the object in the image looks unclear so that a lot of information from the image becomes less clear to see. Image with unclear sharpness becomes less clear, the presence of image sharpening will make the image quality better. Image enhancement is a good step to produce high quality images, high pass filters and sharpening the right finish to produce sharp and quality images. Increasing the exposure in the image makes the image brighter and of higher quality.